(untitled) (Kronika Bydgoska, 2013)
The article is a contribution to the non-compiled history of the Bydgoszcz set design in the 20-year inter-war period. Famous set designers, successful on many Polish stages, worked at the Municipal Theatre in Bydgoszcz at that time. One of them was Feliks Krassowski - a set designer and artist painter staying in Bydgoszcz in the years 1928-1934. Employed as a ”decorator” by Władysław Stoma - the generał manager of the theatre, he designed and made about 140 sets for the drama and music stage. Simultaneously, he participated actively in the city’s artistic-cultural life. He belonged to Bydgoszcz artistic associations and groups, exhibiting paintings and set design projects. Reviews of theatre and music performances, as well as art exhibitions, and a small group of preserved iconographic materials and paintings tell a few words about the versatile works of this eminent artist.